1989
DOI: 10.1021/bi00447a019
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism by purified cytochrome P-450scc is highly stimulated by octyl glucoside and stearic acid exclusively in large unilamellar phospholipid vesicles

Abstract: Cholesterol side-chain cleavage (CSCC) catalyzed by purified bovine adrenal mitochondrial cytochrome P-450scc is highly dependent on the vesicles that supply cholesterol. Six-fold higher rates are achieved with large unilamellar dioleoylphosphatidylcholine vesicles (diameter 150 nm) prepared by octyl glucoside (OG) dialysis (DOPC-LUV) than with small sonicated vesicles (diameter 30 nm) (DOPC-SUV) (Vmax = 25 and 4 min-1, respectively. Extensive dialysis that may remove OG decreased Vmax rates for DOPC-LUV almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…in the order PC(14,10) Ͼ PC(12,8) Ͼ PC(10,6). The observed rates (V max Ͼ 30 min Ϫ1 ) are only comparable with the highest rates reported so far for micellar systems using Tween 20 as detergent (17,19) and for DOPC vesicle systems prepared by octylglucoside dialysis (2). In the latter case the high activity results from residual octylglucoside.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…in the order PC(14,10) Ͼ PC(12,8) Ͼ PC(10,6). The observed rates (V max Ͼ 30 min Ϫ1 ) are only comparable with the highest rates reported so far for micellar systems using Tween 20 as detergent (17,19) and for DOPC vesicle systems prepared by octylglucoside dialysis (2). In the latter case the high activity results from residual octylglucoside.…”
Section: Discussionmentioning
confidence: 62%
“…Both compounds seem to impact the membrane with the same structural property leading to activation of P450SCC via enhancement of CHL binding to P450SCC. Biphasicity in activity is not new; it has been already reported earlier for octylglucoside-reconstituted DOPC vesicles and interpreted as resulting from residual octylglucoside (2). An additional second phase of complex formation also has been reported for DMPC/CL vesicles (7).…”
Section: Table II Stopped Flow Kinetics Of P450scc Incorporation Intomentioning
confidence: 59%
See 1 more Smart Citation
“…To study the chain dependence in greater detail, it would be interesting to use branched PCs with even longer acyl chain substituents in the 2-position; such experiments are now under way. (10,6) or PC (12,8) P450SCC-lipid interaction, vesicles made on the basis of DOPC were often used; applying these a rather high rate of enzymatic activity as compared to DMPC could be observed (1,19,22). Thus, it may be of interest to see to what extent ␣-branched PCs are capable of exerting their influence on the various properties of P450SCC reconstituted into vesicles from DOPC.…”
Section: Effect Of Branched 12-diacyl Pcs On the Catalytic Activity mentioning
confidence: 99%
“…Furthermore, it has been reported previously that reconstitution by both octylglucoside and cholate dialysis results in the formation of two main populations of vesicles, larger and smaller ones with the smaller vesicles containing significantly more P450SCC (31,32). Recently it was reported that the size of the vesicles, which in turn determines the vesicle curvature, has a large influence on the activity (22). Taken together, these findings all suggest that the curvature of the membrane plays a role for the incorporation of P450SCC and thus support our view that polymorphic lipids like CL and the branched PCs could influence P450SCC by maintenance of the membrane curvature at a value optimal for P450SCC activity.…”
mentioning
confidence: 99%